2001
DOI: 10.1046/j.1462-5822.2001.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of microbial proteins contributing to invasion of the blood-brain barrier. MicroReview

Abstract: One of the least understood issues in the pathogenesis and pathophysiology of microbial infection of the central nervous system (CNS) is how microorganisms cross the blood–brain barrier (BBB), which separates brain interstitial space from blood and is formed by the tight junctions of brain microvascular endothelial cells (BMEC). BMEC monolayer and bilayer culture systems have been developed as in vitro models to dissect the mechanisms of adhesion and invasion involved in pathogenesis of CNS infection caused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 70 publications
0
94
0
Order By: Relevance
“…Thus, the brain endothelium likely constitutes a primary barrier to WNV neuroinvasion. Using an established endothelial cell line that exhibits the physiological characteristics of the brain endothelium (16,(22)(23)(24)(25)38) and primary brain endothelial cells, we have demonstrated that WNV-MAD78 can replicate in and traverse the brain endothelium as efficiently as WNV-NY. Our findings are consistent with reports that highly and mildly neuropathogenic strains of Semliki Forest virus replicate to equivalent levels in endothelial cells (39,40), suggesting that the capacity to cross the BBB is not always the determining factor for neuropathogenicity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, the brain endothelium likely constitutes a primary barrier to WNV neuroinvasion. Using an established endothelial cell line that exhibits the physiological characteristics of the brain endothelium (16,(22)(23)(24)(25)38) and primary brain endothelial cells, we have demonstrated that WNV-MAD78 can replicate in and traverse the brain endothelium as efficiently as WNV-NY. Our findings are consistent with reports that highly and mildly neuropathogenic strains of Semliki Forest virus replicate to equivalent levels in endothelial cells (39,40), suggesting that the capacity to cross the BBB is not always the determining factor for neuropathogenicity.…”
Section: Discussionmentioning
confidence: 97%
“…Because replication in brain endothelial cells is sufficient for transport of neuroinvasive strains of WNV across brain microvascular endothelial cells (20), we hypothesized that the decreased neuropathogenicity of WNV-MAD78 was due in part to a deficiency in replication in brain endothelial cells. Therefore, we monitored replication of WNV-NY and WNV-MAD78 in an established human brain microvascular endothelial cell line (HBMEC) that has been widely used as a model to study bacterial and parasitic neuroinvasion (16,(22)(23)(24)(25) and primary brain microvascular endothelial cells (HBMVECs) derived from normal brain cortex tissue (20,26). WNV-NY and WNV-MAD78 replicated at similar rates and to equivalent levels in both cell types, reaching peak titers between 32 and 48 h postinfection ( Fig.…”
Section: Wnv-ny and Wnv-mad78 Replicate To Similar Levels In Neuronalmentioning
confidence: 99%
“…52 On the surface of microglia cells, the TLR-4 predominates, which is known to induce pro-inflammatory processes favoring the development of a Th1 response that is critical in protection against fungi. 53,54 For example, knockout mice for the TLR-4 receptor are susceptible to disseminated candidiasis and reduced clearance of conidias produced by Aspergillus. TLR-2, Dectin-1, and CR-3 on the surface of microglia and macrophages recognize carbohydrates such as mannose and b-glucans on the surface of A. fumigatus and C. albicans.…”
Section: States Of Existencementioning
confidence: 99%
“…An important step in the process of infection by NMEC is the entry into the bloodstream and, once the bacteraemia has reached a certain threshold, the invasion of the central nervous system after traversal of the brain microvascular endothelial cells (BMEC) (Huang & Jong, 2001;Kim, 2001). It has been shown that efficient penetration of E. coli across the blood-brain barrier is mediated by multiple factors.…”
Section: Introductionmentioning
confidence: 99%